2023
DOI: 10.47467/alkharaj.v5i6.2644
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Zakat Produktif, Pengembangan Keterampilan dan Pendampingan Usaha terhadap Minat Wirausahawan Kuliner pada Masa Pandemi:

Abstract: The purpose of this study was to determine the effect of productive zakat, skill development, and business assistance on the interest of culinary entrepreneurs during the pandemic. The researchers used quantitative methods with primary data collection techniques in the form of questionnaires distributed to 33 respondents via Google Forms. The data analysis technique used is multiple linear regression using SPSS version 23. The results of the t-test indicate that the significance value of the productive zakat v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For example,Erlinda (2022) revealed that muzakki trust significantly influences the interest in paying professional zakat at Elzawa. Furthermore,Sabrina & Idrus (2023) analyzed the effect of productive zakat, skills development, and business assistance on culinary entrepreneurs' interest during the LAZ Al Azhar pandemic. Another study by…”
mentioning
confidence: 99%
“…For example,Erlinda (2022) revealed that muzakki trust significantly influences the interest in paying professional zakat at Elzawa. Furthermore,Sabrina & Idrus (2023) analyzed the effect of productive zakat, skills development, and business assistance on culinary entrepreneurs' interest during the LAZ Al Azhar pandemic. Another study by…”
mentioning
confidence: 99%